Mitofusin-2 in ventral striatal D1 neurons regulates effort-based motivation through sex-specific mitochondrial–synaptic reprogramming - Alessandro Chioino; Dogukan H. Ulgen; Olivia Zanoletti; Isabelle Guillot de Suduiraut; Ashley M. Maynard; Elisenda Sanz; Albert Quintana; Simone Astori; Carmen Sandi (Proceedings of the National Academy of Sciences, 2026)
Effort-based motivation varies widely across individuals and affects well-being, yet the molecular and neuronal mechanisms that set motivational capacity remain incompletely understood. Mitochondrial function is emerging as a critical regulator of behavior, and mitofusin-2 (MFN2) is a key mediator of mitochondrial fusion and endoplasmic reticulum–mitochondria coupling. Here, we asked how downregulation of Mfn2 in dopamine receptor type-1-expressing medium spiny neurons (D1-MSNs) contributes to effort-based motivation and stress coping in male and female mice by integrating electrophysiology, neuronal and synaptic morphology, immunohistochemistry, mitochondrial readouts, RNA in situ hybridization, RiboTag, and behavioral analyses. MFN2 deficiency resulted in fragmented dendritic mitochondria and remodeled synaptic inputs in ventral striatal D1-MSNs, with no cellular impact in dorsomedial striatal D1-MSNs. Although MFN2 deficiency elicited sex-dependent synaptic and structural alterations, both sexes showed reduced recruitment of accumbal D1-MSNs during motivated behavior and impaired effort-based motivation and stress coping. Translatome profiling revealed shared depletion of mitochondrial pathways in both sexes, with more pronounced suppression of oxidative phosphorylation and TCA cycle programs in males. Strikingly, only males also exhibited coordinated downregulation of ribosomal programs together with enrichment of synaptic pathways, with high representation of genes regulating glutamate receptor cycling and PSD remodeling, providing a mechanistic framework for the observed synaptic alterations. Pathway-level network inference further supported coupling among mitochondrial, translational, and synaptic programs in males. These findings identify MFN2-dependent mitochondrial integrity in ventral striatal D1-MSNs as a critical determinant of motivational capacity and reveal sex-specific molecular and cellular responses through which mitochondrial dysfunction converges on similar motivational deficits.